STRATEGI PEMASARAN BANK SYARIAH INDONESIA DALAM MENGHADAPI DINAMIKA PERSAINGAN INDUSTRI KEUANGAN - Marsyah Aprilya (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the marketing strategies implemented by Islamic banks in facing competition in the financial industry. The study uses a qualitative descriptive method with a literature study approach, which is to examine secondary data sourced from scientific journals, books, and relevant previous studies. The results of the study indicate that Islamic banks can increase their competitiveness by strengthening customer loyalty, improving product quality and innovation, developing cooperation with various parties, and optimizing promotional activities through conventional and digital media. Effectively and efficiently designed marketing strategies are an important factor for Islamic banks to survive and thrive amid the dynamics of competition in the financial industry.